Influence of Calcination on Mineralogical and Strength Properties of Self Activated Green Material (SAGreM) - Mohd Ridzuan, Assoc. Prof. Dr. Ahmad Ruslan; Muhd Sidek, Muhd Norhasri; Ahmad Anuar, Khairulniza (International Journal of Sustainable Construction Engineering and Technology, 2019)
Concrete is an alkaline activated material consist of lime which contribute from limestone. This SAGreM has potential to be supplementary cementitious material because of the oxide content most similar with cement. SAGreM is a new sources generated from recycling of industrial waste which has similar affect to limestone. The purposed of this study is to investigate the mineralogical composition, particle size distribution and strength development of difference calcination temperature of SAGreM and the effect after activation with water. The mineralogical properties were investigated using by x-ray fluorescence and x-ray diffraction. The mineralogical test results showed that the SAGreM consists of calcite, free lime, and probably a crystal phase. SAGreM creates very well reactivity with water and gain the strength 4.85 MPa at 28 days in ambient condition exposure.